Rent-a-girlfriend. Volume 10 - Miyajima, Reiji (Kodansha Comics, 2021)
"After Kazuya lets slip to his grandmother that she missed Mizuhara's birthday, the matriarch of the Kinoshita family insists on celebrating. She turns Kazuya's upcoming birthday party into a joint one, and suddenly the unlucky guy is scrambling to convince Mizuhara to come. Unfortunately, Ruka also hears about the festivities and demands Kazuya take her. When Mizuhara runs late, Ruka takes the chance to unleash her ultimate win-over-Kazuya's-family-attack!"--Provided by publisher.